Secretory leukocyte protease inhibitor inhibits expression of polymeric immunoglobulin receptor via the NF-κB signaling pathway. Issue 2 (October 2015) - Mikami, Yoshikazu; Iwase, Takashi; Komiyama, Yusuke; Matsumoto, Naoyuki; Oki, Hidero; Komiyama, Kazuo
Highlights: SLPI stimulation decreased the pIgR expression level. pIgR expression level was higher in SLPI-deficient cells than in wild-type cells. SLPI increased IκBβ expression level, and suppressed NF-κB transcriptional activity. SLPI down-regulates pIgR expression through the NF-κB signaling pathway. Abstract: Polymeric immunoglobulin receptor (pIgR) plays an important role in mucosal immune systems. Secretory immunoglobulin A, composed of secretory component of pIgR and a dimeric form of immunoglobulin A, is secreted on mucosal surfaces and serves as a biological defense factor. pIgR gene expression is reportedly induced by activation of the transcription factor nuclear factor (NF)-κB. On the other hand, secretory leukocyte protease inhibitor (SLPI) is a glycoprotein that functions as a serine protease inhibitor. In alveolar epithelial cells, SLPI increases the level of IκBβ, which indicates that it is an inhibitor of NF-κB at the protein level. Taken together, SLPI may regulate pIgR expression; however, the specific mechanism by which this occurs is unclear. Therefore, the aim of this study was to elucidatethe influence of SLPI on pIgR expression.SLPI and pIgR localized in goblet cells and ciliated epithelial cells of the gastrointestinal tract, respectively. No cells were detected in which SLPI and pIgR were co-expressed. In addition, recombinant human SLPI stimulation of an epithelial cell line (HT-29) decreased the pIgR expression. The pIgR expression was also higher in SLPI-deficient Ca9-22 cells than in wild-type Ca9-22 cells. Furthermore, a luciferase assay using a NF-κB reporter plasmid and real-time RT-PCR analysis indicated that when SLPI was present, the transcriptional activity of NF-κB protein was suppressed, which was accompanied by anincrease in the protein, but not the mRNA, expression of IκBβ. These results demonstrate that SLPI down-regulates pIgR expression through the NF-κB signaling pathway by inhibiting degradation of IκBβ protein.